2018
DOI: 10.1016/j.mce.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the sexually dimorphic dexamethasone transcriptome in mouse cerebral cortical and hypothalamic embryonic neural stem cells

Abstract: Fetal exposure to synthetic glucocorticoids reprograms distinct neural circuits in the developing brain, often in a sex-specific manner, via mechanisms that remain poorly understood. To reveal whether such reprogramming is associated with select molecular signatures, we characterized the transcriptome of primary, embryonic mouse cerebral cortical and hypothalamic neural progenitor/stem cells derived from individual male and female embryos exposed to the synthetic glucocorticoid, dexamethasone. Gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 32 publications
(55 reference statements)
0
27
0
Order By: Relevance
“…The lateral septum has also a key role in integrating information from affective brain regions, especially from hippocampus and hypothalamus among others (Sheehan et al 2004). Also, the hypothalamus, where DRR1 expression is strongly induced by dexamethasone in hypothalamic neural-progenitor/stem cells derived from mouse embryos (Frahm et al 2016, 2017), integrates inputs from many central and peripheral sources to maintain homeostasis of different organ systems and whole body metabolism (Denton et al 1996). …”
Section: Discussionmentioning
confidence: 99%
“…The lateral septum has also a key role in integrating information from affective brain regions, especially from hippocampus and hypothalamus among others (Sheehan et al 2004). Also, the hypothalamus, where DRR1 expression is strongly induced by dexamethasone in hypothalamic neural-progenitor/stem cells derived from mouse embryos (Frahm et al 2016, 2017), integrates inputs from many central and peripheral sources to maintain homeostasis of different organ systems and whole body metabolism (Denton et al 1996). …”
Section: Discussionmentioning
confidence: 99%
“…To illustrate the utility of the 3D RNA-seq App in analysing multi-factor RNA-seq data from animals, we re-analysed RNA-seq data which studied the effects of dexamethasone treatment on cortical and hypothalamic neural progenitor/stem cells (NPSCs) from male and female mice (Frahm et al, 2018) The RNA-seq data consisted of male and female cortex and hypothalmus cell cultures treated or untreated with dexamethasone, each with three biological replicates (24 samples in total). The study identified differentially expressed genes common and unique to brain region, gender and dexamethasone treatment (Frahm et al, 2018). The same dataset has also been used to demonstrate the improved resolution of differentially expressed genes using Sleuth for transcript-level differential analysis and aggregation of transcript level pvalues to give gene-level p-values (Yi et al, 2018).…”
Section: Application To Rna-seq Analyses In Animalsmentioning
confidence: 99%
“…The same dataset has also been used to demonstrate the improved resolution of differentially expressed genes using Sleuth for transcript-level differential analysis and aggregation of transcript level pvalues to give gene-level p-values (Yi et al, 2018). Using this data, we performed two differential expression comparisons between: 1) the Sleuth/aggregated p-values method (Pimentel et al, 2017;Yi et al, 2018) and 3D RNA-seq and 2) the results of the differential analysis in Frahm et al, (2018) and those generated by 3D RNA-seq expression results.…”
Section: Application To Rna-seq Analyses In Animalsmentioning
confidence: 99%
See 2 more Smart Citations